6(w+1) = -4(5w-5)+8w
First, distribute the -4 to both terms inside the parentheses:
6(w+1) = -20w + 20 + 8w
Now, distribute the 6 to both terms inside the parentheses:
6w + 6 = -20w + 20 + 8w
Combine like terms by adding the w terms:
14w + 6 = 20
Subtract 6 from both sides:
14w = 14
Finally, divide both sides by 14 to solve for w:
w = 1
Solve for W.
6(w+1) = -4(5w-5)+8w
3 answers
incorrect
Apologies for the mistake.
Let's try again.
6(w+1) = -4(5w-5)+8w
First, distribute the -4 to both terms inside the parentheses:
6(w+1) = -20w + 20 + 8w
Now, distribute the 6 to both terms inside the parentheses:
6w + 6 = -20w + 20 + 8w
Combine like terms by adding the w terms:
6w + 6 = -12w + 20
Next, move all terms containing w to one side:
6w + 12w = 20 - 6
Combine like terms:
18w = 14
Divide both sides by 18 to solve for w:
w = 14/18
Simplifying further:
w = 7/9
Let's try again.
6(w+1) = -4(5w-5)+8w
First, distribute the -4 to both terms inside the parentheses:
6(w+1) = -20w + 20 + 8w
Now, distribute the 6 to both terms inside the parentheses:
6w + 6 = -20w + 20 + 8w
Combine like terms by adding the w terms:
6w + 6 = -12w + 20
Next, move all terms containing w to one side:
6w + 12w = 20 - 6
Combine like terms:
18w = 14
Divide both sides by 18 to solve for w:
w = 14/18
Simplifying further:
w = 7/9